Update on Tools and Techniques in Computer-Assisted Surgery - Nichols, Emma Hitt (MD Conference Express, 2015)
In a session focusing on computer-assisted surgery, 6 presenters covered the new options for tools and techniques and the evidence for different approaches. Overall, these new tools and approaches can improve accuracy, reduce radiation exposure, potentially shorten operating times, and reduce costs.